The Butterfly lion - "Morpurgo , Michael" (Harper Collins Publishers London, 1996)
The Butterfly Lion is a classic children's tale by Michael Morpurgo1. The story follows Bertie, who rescues an orphaned white lion cub from the African veld. They are inseparable until Bertie is sent to boarding school far away in England and the lion is sold to a circus21. Bertie escapes from his school and meets Millie, and the two become fast friends, flying kites together3. The butterfly lion ensures that their friendship will never be forgotten2.
Keywords: Children fiction -- Pictorial